Discovery, synthesis and biochemical profiling of purine-2, 6-dione derivatives as inhibitors of the human poly(A)-selective ribonuclease Caf1. Issue 19 (1st October 2015) - Jadhav, Gopal P.; Kaur, Ishwinder; Maryati, Maryati; Airhihen, Blessing; Fischer, Peter M.; Winkler, G. Sebastiaan
Graphical abstract